Modeling of non-thermal fractions formed in the extended hydrogen corona at Mars - Shematovich, Valery; Bisikalo, Dmitry (Frontiers in Astronomy and Space Sciences, 2025)
Solar forcing on the upper atmospheres of terrestrial planets occurs through both the absorption of soft X-ray and extreme ultraviolet (XUV) solar radiation and the influx of solar wind plasma resulting in the formation of an extended neutral corona populated by suprathermal (hot) H, C, N and O atoms. Observations by the Imaging UV Spectrograph (IUVS) onboard of the Mars Atmosphere and Volatile EvolutioN (MAVEN) space mission at Mars confirmed the presence of an extended corona containing both thermal and suprathermal (formally with kinetic energies below 10 eV) fractions of hydrogen, carbon, and oxygen atoms. The solar wind influx also produces super-thermal atoms—energetic neutral atoms (ENAs; kinetic energies >10 eV)—via charge exchange between high-energy solar wind protons and coronal thermal neutrals. These ENAs transfer solar wind energy into the Martian neutral atmosphere. Notably, this charge-exchange process serves as an active aeronomic mechanism for generating supra- and super-thermal hydrogen populations in Mars’ extended corona and may act as a potential driver for similar phenomena on other planets. The spatial and energy distributions of both non-thermal atomic hydrogen populations in the Martian extended corona were computed using kinetic Monte Carlo models. These non-thermal H fractions must be considered when interpreting remote observations of planetary coronae. Our calculations reveal that non-thermal escape rates can reach ∼26% of the thermal escape rate during aphelion and solar minimum conditions. This finding has significant implications for Mars’ atmospheric evolution: while current escape rates are modulated by solar activity, the more active young Sun likely drove substantially higher non-thermal escape. This mechanism may have played a key role in Mars’ long-term water loss.